(untitled) - Lovett, Andrew (Boca Raton, 2008)
This book takes an interdisciplinary look at the use of GIS for environmental decision making, emphasizing the importance of matters related to data, analysis, and modeling tools, as well as stakeholder participation. The first section stresses the ability to integrate data from different sources as a defining characteristic of GIS. The second section gives examples on the use of GIS for suitability mapping and strategic planning exercises through illustrative examples. The last section of the book examines the use of GIS-based techniques to facilitate public participation in the decision-making process, and overviews developments in the integration of GIS, modeling, and 3d landscape visualization techniques. Material originated at an April 2004 conference held at the University of East Anglia, UK. The original conference papers have been reviewed and revised for publication, and two other invited contributions are included.
Keywords: Environmental policy,Environmental sciences,Geographic information systems,Môi trường; Decision making,Information technology,Equipment and supplies